ASUHAN KEBIDANAN MULAI KEHAMILAN TRIMESTER III SAMPAI DENGAN NIFAS DAN KB PADA NY.“J” DI TPMB ULFA JULAILAH, SST DESA MLARAS KECAMATAN SUMOBITO KABUPATEN JOMBANG - Dewi Triloka Wulandari; Faridah Nur Jannah Lewa (Jurnal Cakrawala Ilmiah, 2023)
Pregnancy, Maternity, Postpartum and Neonates are a physiological process, but sometimes not as expected. This process can cause problems that can lead to increased maternal mortality and infant mortality. In Jombang Province, AKI in 2019 reached 71,63% and AKB reached 9,46% (Dinkes Jombang, 2019). Factors causing high AKI are bleeding, preeclampsia, and infection, while in newborns are asphyxia, LBW, neonatorum infection. The care of Continuity Of Care carried out by the author starts from the trimester III pregnant women, maternity, postpartum period, Neonates and ongoing family planning using midwifery care standards. Care given at PMB Ulfah Julailah starts from March 15, 2020 to June 11, 2020. Obstetric care visits are carried out at the mother's home and at PMB with 3 times pregnant visits, postpartum 4 times, newborns 3 times and 2 times birth control. Mrs "J" was referred to and delivered in the hospital with an indication of KPD. During the postpartum visit the mother developed anemia and positive urine protein. At the neonatal visit the infant had physiologic stunt and jaundice. Continuity Of Care midwifery care results that have been done to Mrs. J during pregnancy, maternity, puerperium, newborns, and family planning results of the examination within normal limits, there is no complication that accompanies. It is hoped that she can apply the counseling that has been given during midwifery care so that the condition of the mother and baby remains healthy and prevents the occurrence of complications until death.